Molecular mapping of stem and leaf rust resistance in wheat - Khan, R. R.; Bariana, Harbans S.; Dholakia, Bhushan B.; Naik, S. V.; Lagu, Meena D.; Rathjen, A. J.; Bhavani, Sridhar; Gupta, V. S. (Theoretical and Applied Genetics, 2005)
Stem rust caused by Puccinia graminis f. sp. tritici Eriks and Henn and leaf rust caused by Puccinia triticina Rob. ex Desm. are major constraints to wheat production worldwide. In the present study, F-4-derived SSD population, developed from a cross between Australian cultivars `Schomburgk' and `Yarralinka', was used to identify molecular markers linked to rust resistance genes Lr3a and Sr22. A total of 1,330 RAPD and 100 ISSR primers and 33 SSR primer pairs selected on the basis of chromosomal locations of these genes were used. The ISSR marker UBC 840(540) was found to be linked with Lr3a in repulsion at a distance of 6.0 cM. Markers cfa2019 and cfa2123 flanked Sr22 at a distance of 5.9 cM (distal) and 6.0 cM (proximal), respectively. The use of these markers in combination would predict the presence or absence of Sr22 in breeding populations. A previously identified PCR-based diagnostic marker STS638 linked to Lr20 was validated in this population. This marker showed a recombination value of 7.1 cM with Lr20.

Molecular genetic mapping of quantitative trait loci associated with loaf volume in hexaploid wheat (Triticum aestivum) - Elangovan, M.; Rai, R.; Dholakia, Bhushan B.; Lagu, Meena D.; Tiwari, R.; Gupta, R. K.; Rao, V. S.; Roeder, M. S.; Gupta, V. S. (Journal of Cereal Science, 2008)
Major efforts in wheat research are being made to improve the yield and quality of wheat. Loaf volume (Lv) is the main quality parameter deciding the bread making potential of wheat. To genetically dissect quantitative trait loci (QTLs) for Lv, a Recombinant Inbred Line (RIL) population (F-8) was developed from a cross between two Indian wheat varieties ``H 1977'' and ``HD 2329''. A total of 914 SSR and 100 ISSR primers were used for molecular analysis and the genetic map comprising 19 chromosomes was constructed with 202 SSR markers and 2 HMW glutenin subunit loci: Glu-B1 and Glu-B1. The phenotypic data were collected from six environments including three different agro-climatic zones for 2 consecutive years. Dissection of Lv through AMMI model revealed significant G x E variance for the trait. QTL analysis was performed using composite interval mapping. A total of 30 QTLs for Lv were detected and significant QTLs were identified on 6B and 6D chromosomes; 1B, 1D, 2A, 3A, 513 and 5D also contributed genetically to Lv. Association between 6B and 6D QTLs and variable expression of gliadins on group 6 chromosomes were discussed. QTLs detected in this study were compared with other QTL analysis in wheat. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: breadmaking; loaf volume; QTL; SSR; wheat quality

Differential accumulation of gliadin proteins in wheat grain of RILs grown at two different agroclimatic conditions and their effect on loaf volume - Elangovan, M.; Dholakia, Bhushan B.; Gaikwad, S. M.; Gupta, V. S. (Australian Journal of Crop Science, 2010)
The end use of wheat depends on the quality and quantity of protein accumulated in the grain during the grain filling stage. Gliadin families of proteins are proved to affect the bread making quality (BMQ) by affecting the rheology and functionality of dough. The gliadin accumulation was analysed using Indian genotypes grown in two diverse agro climatic zones. About 16 RILs along with their parents HI977 and HD2329 revealed significant difference in accumulation of all gliadin fractions. High accumulation of alpha and beta gliadin with low level of gamma gliadin was observed for Kota as compared to Pune location. However, this significant difference in gliadin accumulation due to environment, did not affect the loaf volume performance of the RILs at statistically significant level.
Keywords: loaf volume (Lv); RP-HPLC; Wheat protein

Molecular insights into resistance mechanisms of lepidopteran insect pests against toxicants - Dawkar, Vishal V.; Chikate, Yojana R.; Lomate, Purushottam R.; Dholakia, Bhushan B.; Gupta, Vidya S.; Giri, Ashok P. (Journal of Proteome Research, 2013)
Insect pests remain a major reason for crop loss worldwide despite extensive use of chemical insecticides. More than B 50% of all insecticides are organophosphates, followed by synthetic pyrethroids, organochlorines, carbamates, and biopesticides, and their continued use may have many environmental, agricultural, medical, and socioeconomic issues. Importantly, only a countable number of insects have acquired the status of crop pests, mostly due to monoculture of crop plants and polyphagous nature of the insects. We focus on A adaptations of Lepidopteran insects to phytochemicals and synthetic pesticides in native and modern agricultural systems. Because of heavy use of chemical insecticides, a strong selection pressure is imposed on insect populations, resulting in the emergence of resistance against candidate compound(s). Current knowledge suggests that insects generally implement a three-tier system to overcome the effect of toxic compounds at physiological, biochemical, and genetic levels. Furthermore, we have discussed whether the adaptation to phytochemicals provides an advantage to the insect while encountering synthetic insecticide molecules. Specific metabolic pathways employed by insects to convert deterrents into less toxic forms or their removal from the system are highlighted. Using the proteomics approach, insect proteins interacting with insecticides can be identified, and their modification in resistant insects can be characterized. Also, systems biology studies can offer useful cues to decipher the molecular networks participating in the metabolism of detrimental compounds.
Keywords: field crops; insect-pests; insecticide; Lepidoptera; proteomics; resistance mechanisms

Molecular mapping of leaf rust resistance gene Lr15 in hexaploid wheat - Dholakia, Bhushan B.; Rajwade, A. V.; Hosmani, P.; Khan, R. R.; Chavan, S.; Reddy, D. M. R.; Lagu, Meena D.; Bansal, Urmil K.; Saini, R. G.; Gupta, V. S. (Molecular Breeding, 2013)
Leaf rust is a widespread and commonly occurring rust disease of wheat. Genetic resistance is the most economical method of reducing losses due to leaf rust. Lr15 has been shown to be present on wheat chromosome 2D and is reported to be a seedling resistance gene. However, tightly linked markers associated with Lr15 have not been reported to date. To identify molecular markers linked to Lr15, an F-2 mapping population of Thatcher x Thatcher-Lr15 was generated. Available wheat simple sequence repeat markers were utilized in parental screening and polymorphic markers were used to analyze the entire population of 221 plants. Phenotypic evaluations of the F-2-derived F-3 progenies with Puccinia triticina Eriks. pathotype 162A (93R15) confirmed the monogenic inheritance of Lr15. The linkage group representing chromosome 2DS was constructed at LOD 4.0 which revealed the closest flanking markers Xgwm4562 and Xgwm102 at a distance of 3.1 and 9.3 cM, respectively. Furthermore, utilization of these flanking markers in combination has successfully identified wheat lines with or without Lr15. These markers could potentially be useful in gene pyramiding with other genes to enhance rust resistance in wheat.
Keywords: Disease resistance; Leaf rust; Marker-assisted selection; Simple sequence repeat; Wheat

Evaluation of genetic variability in Symplocos laurina Wall. from two biodiversity hotspots of India - Bhagwat, Rasika M.; Banu, Sofia; Dholakia, Bhushan B.; Kadoo, Narendra Y.; Lagu, Meena D.; Gupta, Vidya S. (Plant Systematics and Evolution, 2014)
Symplocos laurina Wall., an important medicinal tree species, is one of the pioneering plants for establishment of shola forest ecosystem. We analyzed 208 accessions of S. laurina from 13 populations belonging to three ecoregions in India namely, Western Ghats, Eastern Ghats and Northeast India, to comment on the genetic diversity and population structure of the species. Of the 100 inter simple sequence repeat primers screened, eight were selected based on their clear and reproducible polymorphic patterns. These eight ISSR primers produced on an average 1,014 bands from 208 accessions, of which 6.58 % were rare bands, 55.96 % were shared bands and 37.46 % were similar bands. The primers, UBC835 and UBC880, amplified the highest number of polymorphic loci (16), while the primer UBC852 amplified the least number of amplicons (9). The values for total genetic diversity (H-T) and the average heterozygosity (H-S) were 0.3407 and 0.2263, respectively; while the coefficient of genetic differentiation (G(ST)) was 0.3358. Within-population variance was higher (68 %) than among-population variance (17 %), indicating high intra-population genetic diversity. These populations were grouped according to their geographical location in cluster analysis. Mantel test also showed significant positive correlation between genetic and geographical distances. The present study revealed the importance of the Palghat gap in South India in shaping the distribution of genetic diversity in S. laurina.
Keywords: Biodiversity hotspots; Genetic diversity; ISSR; Palghat gap; Symplocos laurina

Agriproteomics of bread wheat: comparative proteomics and network analyses of grain size variation - Dawkar, Vishal V.; Dholakia, Bhushan B.; Gupta, Vidya S. (OMICS-A Journal Of Integrative Biology, 2015)
Agriproteomics signifies the merging of agriculture research and proteomics systems science and is impacting plant research and societal development. Wheat is a frequently consumed foodstuff, has highly variable grain size that in effect contributes to wheat grain yield and the end-product quality. Very limited information is available on molecular basis of grain size due to complex multifactorial nature of this trait. Here, using liquid chromatography-mass spectrometry, we investigated the proteomics profiles from grains of wheat genotypes, Rye selection 111 (RS111) and Chinese spring (CS), which differ in their size. Significant differences in protein expression were found, including 33 proteins uniquely present in RS111 and 32 only in CS, while 54 proteins were expressed from both genotypes. Among differentially expressed proteins, 22 were upregulated, while 21 proteins were downregulated in RS111 compared to CS. Functional classification revealed their role in energy metabolism, seed storage, stress tolerance and transcription. Further, protein interactive network analysis was performed to predict the targets of identified proteins. Significantly different interactions patterns were observed between these genotypes with detection of proteins such as Cyp450, Sus2, and WRKY that could potentially affect seed size. The present study illustrates the potentials of agriproteomics as a veritable new frontier of plant omics research.

Genotype x environment interactions and QTL clusters underlying dough rheology traits in triticum aestivum L. - Prashant, Ramya; Mani, Elangovan; Rai, Richa; Gupta, R. K.; Tiwari, Ratan; Dholakia, Bhushan B.; Oak, Manoj; Roeder, Marion; Kadoo, Narendra Y.; Gupta, Vidya (Journal of Cereal Science, 2015)
Genetic dissection of dough rheology traits (DRT) in hexaploid wheat was carried out using nine mixograph characters evaluated in two consecutive years in three agro-climatic zones in India in an RIL population (HI977 x HD2329). Pearson correlations determined in each year-location indicated 15 stable trait inter-relationships among them but inconsistent correlations with loaf volume (LV) were observed. Using AMMI analysis we derived patterns in G x E interactions (GEI) indicating 6-47% contribution for the DRT. Composite interval mapping using a linkage map of 202 SSR markers identified 144 DRT QTLs of which, 96 were detected in single- and the rest in two to five year-locations. Sixteen QTL clusters located on ten chromosomes were identified and only three of them on chromosomes 1B, 5B and 6D involved LV QTLs. For each trait, majority of the DRT QTLs detected in single as well as multiple environments showed location-specificity and suggested that owing to GEI, breeding for wheat dough quality might need careful selection of QTLs targeted for individual agro-climatic zones. The inconsistent correlations of DRT and LV and differential locations of their QTLs in this population corroborated that using dough rheological traits alone to predict LV might pose challenges during wheat improvement. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: AMMI analysis; Dough rheology; Mixograph; QTL

Metabolic profiling of chickpea-Fusarium interaction identifies differential modulation of disease resistance pathways - Kumar, Yashwant; Dholakia, Bhushan B.; Panigrahi, Priyabrata; Kadoo, Narendra Y.; Giri, Ashok P.; Gupta, Vidya S. (Phytochemistry, 2015)
Chickpea is the third most widely grown legume in the world and mainly used as a vegetarian source of human dietary protein. Fusarium wilt, caused by Fusarium oxysporum f. sp. ciceri (Foc), is one of the major threats to global chickpea production. Host resistance is the best way to protect crops from diseases; however, in spite of using various approaches, the mechanism of Foc resistance in chickpea remains largely obscure. In the present study, non-targeted metabolic profiling at several time points of resistant and susceptible chickpea cultivars using high-resolution liquid chromatography-mass spectrometry was applied to better understand the mechanistic basis of wilt resistance or susceptibility. Multivariate analysis of the data (OPLS-DA) revealed discriminating metabolites in chickpea root tissue after Foc inoculation such as flavonoids, isoflavonoids, alkaloids, amino acids and sugars. Foc inoculated resistant plants had more flavonoids and isoflavonoids along with their malonyl conjugates. Many antifungal metabolites that were induced after Foc infection viz, aurantion-obstine beta-glucosides and querecitin were elevated in resistant cultivar. Overall, diverse genetic and biochemical mechanisms were operational in the resistant cultivar for Foc defense as compared to the susceptible plant. The resistant chickpea plants employed the above-mentioned metabolic pathways as potential defense strategy against Foc. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Chickpea; Fusarium wilt; LC-MS; Metabolomics; OPLS-DA; Phytoalexin

Two new potential barcodes to discriminate dalbergia species - Bhagwat, Rasika M.; Dholakia, Bhushan B.; Kadoo, Narendra Y.; Balasundaran, M.; Gupta, Vidya S. (Plos One, 2015)
DNA barcoding enables precise identification of species from analysis of unique DNA sequence of a target gene. The present study was undertaken to develop barcodes for different species of the genus Dalbergia, an economically important timber plant and is widely distributed in the tropics. Ten Dalbergia species selected from the Western Ghats of India were evaluated using three regions in the plastid genome (matK, rbcL, trnH-psbA), a nuclear transcribed spacer (nrITS) and their combinations, in order to discriminate them at species level. Five criteria: (i) inter and intraspecific distances, (ii) Neighbor Joining (NJ) trees, (iii) Best Match (BM) and Best Close Match (BCM), (iv) character based rank test and (v) Wilcoxon signed rank test were used for species discrimination. Among the evaluated loci, rbcL had the highest success rate for amplification and sequencing (97.6%), followed by matK (97.0%), trnH-psbA (94.7%) and nrITS (80.5%). The inter and intraspecific distances, along with Wilcoxon signed rank test, indicated a higher divergence for nrITS. The BM and BCM approaches revealed the highest rate of correct species identification (100%) with matK, matK+rbcL and matK+trnH-psb loci. These three loci, along with nrITS, were further supported by character based identification method. Considering the overall performance of these loci and their ranking with different approaches, we suggest matK and matK+rbcL as the most suitable barcodes to unambiguously differentiate Dalbergia species. These findings will potentially be helpful in delineating the various species of Dalbergia genus, as well as other related genera.

Characterization of roseomonas and nocardioides spp. for arsenic transformation - Bagade, Aditi V.; Bachate, Sachin P.; Dholakia, Bhushan B.; Giri, Ashok P.; Kodam, Kisan M. (Journal of Hazardous Materials, 2016)
The metalloid arsenic predominantly exists in the arsenite [As(III)] and arsenate [As(V)]. These two forms are respectively oxidized and reduced by microbial redox processes. This study was designed to bioprospect arsenic tolerating bacteria from Lonar lake and to characterize their arsenic redoxing ability. Screening of sixty-nine bacterial species isolated from Lonar lake led to identification of three arsenic oxidizing and seven arsenic-reducing species. Arsenite oxidizing isolate Roseomonas sp. L-159a being closely related to Roseomonas cervicalis ATCC 49957 oxidized 2 mM As(III) in 60 h. Gene expression of large and small subunits of arsenite oxidase respectively showed 15- and 17-fold higher expression. Another isolate Nocardioides sp. L-37a formed a clade with Nocardioides ghangwensis JC2055, exhibited normal growth with different carbon sources and pH ranges. It reduced 2 mM As(V) in 36 h and showed constitutive expression of arsenate reductase which increased over 4-fold upon As(V) exposure. Genetic markers related to arsenic transformation were identified and characterized from the two isolates. Moderate resistance against the arsenicals was exhibited by the two isolates in the range of 1-5 mM for As(III) and 1-200 mM for As(V). Altogether we provide multiple evidences to indicate that Roseomonas sp. and Nocardioides sp. exhibited arsenic transformation ability. (C) 2016 Elsevier B.V. All rights reserved.

Comparative functional characterization of eugenol synthase from four different ocimum species: implications on eugenol accumulation - Anand, Atul; Jayaramaiah, Ramesha H.; Beedkar, Supriya D.; Singh, Priyanka A.; Joshi, Rakesh S.; Mulani, Fayaj A.; Dholakia, Bhushan B.; Punekar, Sachin A.; Gade, Wasudeo N.; Thulasiram, Hirekodathakallu V.; Giri, Ashok P. (Biochimica Et Biophysica Acta-Proteins and Proteomics, 2016)
Isoprenoids and phenylpropanoids are the major secondary metabolite constituents in Ocimum genus. Though enzymes from phenylpropanoid pathway have been characterized from few plants, limited information exists on how they modulate levels of secondary metabolites. Here, we performed phenylpropanoid profiling in different tissues from five Ocimum species, which revealed significant variations in secondary metabolites including eugenol, eugenol methyl ether, estragole and methyl cinnamate levels. Expression analysis of eugenol synthase (EGS) gene showed higher transcript levels especially in young leaves and inflorescence; and were positively correlated with eugenol contents. Additionally, transcript levels of coniferyl alcohol acyl transferase, a key enzyme diverting pool of substrate to phenylpropanoids, were in accordance with their abundance in respective species. In particular, eugenol methyl transferase expression positively correlated with higher levels of eugenol methyl ether in Ocimum tenuiflorum. Further, EGSs were functionally characterized from four Ocimum species varying in their eugenol contents. Kinetic and expression analyses indicated, higher enzyme turnover and transcripts levels, in species accumulating more eugenol. Moreover, biochemical and bioinformatics studies demonstrated that coniferyl acetate was the preferred substrate over coumaryl acetate when used, individually or together, in the enzyme assay. Overall, this study revealed the preliminary evidence for varied accumulation of eugenol and its abundance over chavicol in these Ocimum species. Current findings could potentially provide novel insights for metabolic modulations in medicinal and aromatic plants. (C) 2016 Elsevier B.V. All rights reserved.

Fusarium oxysporum mediates systems metabolic reprogramming of chickpea roots as revealed by a combination of proteomics and metabolomics - Kumar, Yashwant; Zhang, Limin; Panigrahi, Priyabrata; Dholakia, Bhushan B.; Dewangan, Veena; Chavan, Sachin G.; Kunjir, Shrikant M.; Wu, Xiangyu; Li, Ning; Rajmohanan, Pattuparambil R.; Kadoo, Narendra Y.; Giri, Ashok P.; et al. (Plant Biotechnology Journal, 2016)
Molecular changes elicited by plants in response to fungal attack and how this affects plant-pathogen interaction, including susceptibility or resistance, remain elusive. We studied the dynamics in root metabolism during compatible and incompatible interactions between chickpea and Fusarium oxysporum f. sp. ciceri (Foc), using quantitative label-free proteomics and NMR-based metabolomics. Results demonstrated differential expression of proteins and metabolites upon Foc inoculations in the resistant plants compared with the susceptible ones. Additionally, expression analysis of candidate genes supported the proteomic and metabolic variations in the chickpea roots upon Foc inoculation. In particular, we found that the resistant plants revealed significant increase in the carbon and nitrogen metabolism; generation of reactive oxygen species (ROS), lignification and phytoalexins. The levels of some of the pathogenesis-related proteins were significantly higher upon Foc inoculation in the resistant plant. Interestingly, results also exhibited the crucial role of altered Yang cycle, which contributed in different methylation reactions and unfolded protein response in the chickpea roots against Foc. Overall, the observed modulations in the metabolic flux as outcome of several orchestrated molecular events are determinant of plant's role in chickpea-Foc interactions.
Keywords: Chickpea; fusarium oxysporum; Metabolomics; NMR; plant-pathogen interaction; proteomics

Dynamic metabolic reprogramming of steroidal glycol-alkaloid and phenylpropanoid biosynthesis may impart early blight resistance in wild tomato (Solanum arcanum Peralta) - Shinde, Balkrishna A.; Dholakia, Bhushan B.; Hussain, Khalid; Panda, Sayantan; Meir, Sagit; Rogachev, Ilana; Aharoni, Asaph; Giri, Ashok P.; Kamble, Avinash C. (Plant Molecular Biology, 2017)
Alternaria solani severely affects tomato (Solanum lycopersicum L.) yield causing early blight (EB) disease in tropical environment. Wild relative, Solanum arcanum Peralta could be a potential source of EB resistance; however, its underlying molecular mechanism largely remains unexplored. Hence, non-targeted metabolomics was applied on resistant and susceptible S. arcanum accessions upon A. solani inoculation to unravel metabolic dynamics during different stages of disease progression. Total 2047 potential metabolite peaks (mass signals) were detected of which 681 and 684 metabolites revealed significant modulation and clear differentiation in resistant and susceptible accessions, respectively. Majority of the EB-triggered metabolic changes were active from steroidal glycol-alkaloid (SGA), lignin and flavonoid biosynthetic pathways. Further, biochemical and gene expression analyses of key enzymes from these pathways positively correlated with phenotypic variation in the S. arcanum accessions indicating their potential role in EB. Additionally, transcription factors regulating lignin biosynthesis were also up-regulated in resistant plants and electrophoretic mobility shift assay revealed sequence-specific binding of rSaWRKY1 with MYB20 promoter. Moreover, transcript accumulation of key genes from phenylpropanoid and SGA pathways along with WRKY and MYB in WRKY1 transgenic tomato lines supported above findings. Overall, this study highlights vital roles of SGAs as phytoalexins and phenylpropanoids along with lignin accumulation unrevealing possible mechanistic basis of EB resistance in wild tomato.

WRKY1 acts as a key component improving resistance against Alternaria solani in wild tomato, Solanum arcanum Peralta - Shinde, Balkrishna A.; Dholakia, Bhushan B.; Hussain, Khalid; Aharoni, Asaph; Giri, Ashok P.; Kamble, Avinash C. (Plant Biotechnology Journal, 2018)
Early blight (EB), caused by Alternaria solani, is a major threat to global tomato production. In comparison with cultivated tomato (Solanum lycopersicum), a wild relative, S.arcanum exhibits strong resistance against EB. However, molecular cascades operating during EB resistance in wild or cultivated tomato plants are largely obscure. Here, we provide novel insight into spatio-temporal molecular events in S.arcanum against A.solani. Transcriptome and co-expression analysis presented 33-WRKYs as promising candidates of which 12 SaWRKYs displayed differential expression patterns in resistant and susceptible accessions during EB disease progression. Among these, SaWRKY1 exhibited induced expression with significant modulation in xyloglucan endotrans hydrolase 5 (XTH5) and MYB2 expressions that correlated with the disease phenotypes. Electro-mobility shift assay confirmed physical interaction of recombinant SaWRKY1 to SaXTH5 and SaMYB2 promoters. Comparative WRKY1 promoter analysis between resistant and susceptible plants revealed the presence of crucial motifs for defence mechanism exclusively in resistant accession. Additionally, many defence-related genes displayed significant expression variations in both the accessions. Further, WRKY1 overexpressing transgenic plants exhibited higher levels of EB resistance while RNAi silencing lines had increased susceptibility to A.solani with altered expression of XTH5 and MYB2. Overall, these findings demonstrate the positive influence of WRKY1 in improving EB resistance in wild tomato and this could be further utilized as a potential target through genetic engineering to augment protection against A.solani in crop plants.
Keywords: Alternaria solani; early blight; Solanum arcanum; Tomato; WRKY1; XTH5

Flower bud proteome reveals modulation of sex-biased proteins potentially associated with sex expression and modification in dioecious Coccinia grandis - Devani, Ravi Suresh; Chirmade, Tejas; Sinha, Sangram; Bendahmane, Abdelhafid; Dholakia, Bhushan B.; Banerjee, Anjan Kumar; Banerjee, Jayeeta (BMC Plant Biology, 2019)
BackgroundDioecy is an important sexual system wherein, male and female flowers are borne on separate unisexual plants. Knowledge of sex-related differences can enhance our understanding in molecular and developmental processes leading to unisexual flower development. Coccinia grandis is a dioecious species belonging to Cucurbitaceae, a family well-known for diverse sexual forms. Male and female plants have 22A+XY and 22A+XX chromosomes, respectively. Previously, we have reported a gynomonoecious form (22A+XX) of C. grandis bearing morphologically hermaphrodite flowers (GyM-H) and female flowers (GyM-F). Also, we have showed that foliar spray of AgNO3 on female plant induces morphologically hermaphrodite bud development (Ag-H) despite the absence of Y-chromosome.ResultsTo identify sex-related differences, total proteomes from male, female, GyM-H and Ag-H flower buds at early and middle stages of development were analysed by label-free proteomics. Protein search against the cucumber protein sequences (Phytozome) as well as in silico translated C. grandis flower bud transcriptome database, resulted in the identification of 2426 and 3385 proteins (FDR <= 1%), respectively. The latter database was chosen for further analysis as it led to the detection of higher number of proteins. Identified proteins were annotated using BLAST2GO pipeline. SWATH-MS-based comparative abundance analysis between Female_Early_vs_Male_Early, Ag_Early_vs_Female_Early, GyM-H_Middle_vs_Male_Middle and Ag_Middle_vs_ Male_Middle led to the identification of 650, 1108, 905 and 805 differentially expressed proteins, respectively, at fold change >= 1.5 and P <= 0.05. Ethylene biosynthesis-related candidates as highlighted in protein interaction network were upregulated in female buds compared to male buds. AgNO3 treatment on female plant induced proteins related to pollen development in Ag-H buds. Additionally, a few proteins governing pollen germination and tube growth were highly enriched in male buds compared to Ag-H and GyM-H buds.ConclusionOverall, current proteomic analysis provides insights in the identification of key proteins governing dioecy and unisexual flower development in cucurbitaceae, the second largest horticultural family in terms of economic importance. Also, our results suggest that the ethylene-mediated stamen inhibition might be conserved in dioecious C. grandis similar to its monoecious cucurbit relatives. Further, male-biased proteins associated with pollen germination and tube growth identified here can help in understanding pollen fertility.
Keywords: Coccinia grandis; Dioecy; Pollen fertility; proteomics; Sex modification; Stamen arrest

Terpene profiling, transcriptome analysis and characterization of cis–terpineol synthase from Ocimum - Anand, Atul; Jayaramaiah, Ramesha H.; Beedkar, Supriya D.; Dholakia, Bhushan B.; Lavhale, Santosh G.; Punekar, Sachin A.; Gade, Wasudeo N.; Thulasiram, Hirekodathakallu V.; Giri, Ashok P. (Physiology and Molecular Biology of Plants, 2019)
Ocimum species produces a varied mix of different metabolites that imparts immense medicinal properties. To explore this chemo-diversity, we initially carried out metabolite profiling of different tissues of five Ocimum species and identified the major terpenes. This analysis broadly classified these five Ocimum species into two distinct chemotypes namely, phenylpropanoid-rich and terpene-rich. In particular, -caryophyllene, myrcene, limonene, camphor, borneol and selinene were major terpenes present in these Ocimum species. Subsequently, transcriptomic analysis of pooled RNA samples from different tissues of Ocimum gratissimum, O. tenuiflorum and O. kilimandscharicum identified 38 unique transcripts of terpene synthase (TPS) gene family. Full-length gene cloning, followed by sequencing and phylogenetic analysis of three TPS transcripts were carried out along with their expression in various tissues. Terpenoid metabolite and expression profiling of candidate TPS genes in various tissues of Ocimum species revealed spatial variances. Further, putative TPS contig 19414 (TPS1) was selected to corroborate its role in terpene biosynthesis. Agrobacterium-mediated transient over-expression assay of TPS1 in the leaves of O. kilimandscharicum and subsequent metabolic and gene expression analyses indicated it as a cis–terpineol synthase. Overall, present study provided deeper understanding of terpene diversity in Ocimum species and might help in the enhancement of their terpene content through advanced biotechnological approaches.
Keywords: Agro-infiltration assay; Metabolite profiling; Ocimum; Terpene synthase; Terpenes; Transcriptome

Combinatorial approach through in vitro regeneration and phytochemical profiling of ceropegia media (huber) ans.: a potential way forward in the conservation of an endangered medicinal plant from the western ghats in India - Pandey, Meena; Dholakia, Bhushan B.; Jayaramaiah, Ramesha H.; Punekar, Sachin A.; Giri, Ashok P. (Journal of Plant Growth Regulation, 2020)
Ceropegia mediais an endemic and endangered plant as its propagation through seeds is unreliable due to low germination, slow growth and seedling decay under natural conditions. Also, tubers of this plant are edible serving as carbohydrate source with medicinal values leading to severe population decline in the natural habitat. To provide a sustainable solution, an efficient in vitro propagation protocol along with phytochemical profiling was developed forC. media. Callus cultures were induced from seedling and wild leaf tissues using the most effective Murashige and Skoog's (MS) medium with 2,4-dichlorophenoxyacetic acid (2,4-D; 2 mu M) and sucrose (3%). Somatic embryos were acquired on MS medium with 1 mu M 6-Benzylaminopurine (BAP) and 1 mu M 2,4-D. Conversion into plantlets was attained only from tissue culture-derived seedling leaf (TCDSL) explant. Further, in vitro tuberization was achieved from TCDSL callus with BAP and Naphthalene acetic acid (NAA). AgNO(3)as an elicitor had a positive effect on both fresh and dry weights of callus. Successful acclimatization (58%) was attained after two months resulting in normal phenotype in pots. Further, metabolite profiles of ten different tissues from wild and in vitro plants were compared. Total 82 compounds comprising alkaloids, fatty acids, fatty acid ester, steroids, terpenes and hydrocarbons were identified. Overall, results suggested enhanced production of selected metabolites with in vitro propagation and AgNO3, alleviating the problem of unavailability of planting materials. Thus, the current study might offer potential ways for the conservation of such RED enlisted species asC. media. [GRAHICS]
Keywords: Ceropegia media; GC-MS; Microtuberization; Secondary metabolites; Silver nitrate; somatic embryogenesis

Differential modulation in metabolites revealed with the improvement in the shelf-life of alphonso fruits - Dar, M. Saleem; Dholakia, Bhushan B.; Shanmugam, Haripriya; Gupta, Vidya S.; Subramanian, K. S.; Subramanian, J.; Giri, Ashok P. (Molecular Biotechnology, 2020)
Globally farmers have difficulty in extending the shelf-life of the tropical fruits due to their perishable nature. The present study aimed to assess the effect of hexanal nano-formulation treatment (NFT) on the shelf-life of Alphonso mango. Further, volatilomics was performed to explore the molecular basis of such effect. Untreated and treated fruits were sampled starting from 5th to 21st day after NFT at an interval of 4 days. Moderate changes in visual and digital colour parameters were evident from the intact and dissected fruits of NFT set compared to untreated fruits. Biochemical assays affirmed the phenotypic differences with significant changes in the colour imparting compounds like carotenoids and anthocyanins among them. Further, gas chromatography-mass spectrometry analysis revealed significant qualitative and quantitative variations in the different classes of compounds like lactones, furanones, esters, aldehydes and alcohols. Some of the key metabolites showed differential modulations among the NFT and untreated fruit sets indicating their potential role in various processes, which ultimately might have resulted in delayed ripening of the mango. Overall, this study has demonstrated the beneficial effect of hexanal and identified important metabolites with the enhanced shelf-life in Alphonso that could be useful for farmers and mango-based food/flavour industries.
Keywords: Alphonso; GC-MS; Metabolites; Nano-biotechnology; Nano-formulation; Shelf-life; Volatilomics

Generation of novelties in the genus Ocimum as a result of natural hybridization: a morphological, genetical and chemical appraisal - Gurav, Tanuja P.; Jayaramaiah, Ramesha H.; Punekar, Sachin A.; Dholakia, Bhushan B.; Giri, Ashok P. (Industrial Crops and Products, 2020)
The genus Ocimum is a boutique of a diverse set of specialized metabolites such as terpenoids and phenylpropanoids. Each Ocimum species and its cultivars represent a characteristic chemical profile. The present study explored the two interspecific Ocimum hybrids originating through a serendipitous natural cross between O. kilimandscharicum and O. basilicum. These two novel Ocimum hybrids exhibited intermediate morphological features of two parental species. Inter simple sequence repeats (ISSR) analysis and DNA barcoding with the plastid non-coding trnH-psbA intergenic spacer region reaffirmed unambiguous parental identification and differentiation of these natural hybrids from other available Ocimum species. Consequently, gas chromatographymass spectrometry-based metabolite profiling of two hybrids identified them as specific chemotypes with the presence of a unique blend of specialized metabolites from the parental species, which are either rich in terpenes or phenylpropanoids. Additionally, expression analysis of key genes from terpenoid and phenylpropanoid pathways corroborated with differential metabolite accumulation. Thus, these two Ocimum hybrids represented the novel chemotypes, which could be useful in commercial cultivation to produce novel essential oil and bioactive constituents. Further, the resulting metabolite diversity could have potential industrial applications in the areas of healthcare, bioremediation, and crop protection.
Keywords: Chemotype; DNA barcoding; Inter Simple Sequence Repeats; Interspecific hybrid; O. basilicum; O. kilimandscharicum; Ocimum

High-throughput metabolomic and transcriptomic analyses vet the potential route of cerpegin biosynthesis in two varieties of Ceropegia bulbosa Roxb. - Gharat, Sachin A.; Shinde, Balkrishna A.; Mule, Ravindra D.; Punekar, Sachin A.; Dholakia, Bhushan B.; Jayaramaiah, Ramesha H.; Ramaswamy, Gopalakrishna; Giri, Ashok P. (Planta, 2020)
Ceropegia bulbosa is an important medicinal plant, used in the treatment of various ailments including diarrhea, dysentery, and syphilis. This is primarily attributed to the presence of pharmaceutically active secondary metabolites, especially cerpegin. As this plant belongs to an endemic threatened category, genomic resources are not available hampering exploration on the molecular basis of cerpegin accumulation till now. Therefore, we undertook high-throughput metabolomic and transcriptomic analyses using different tissues from two varieties namely, C. bulbosa var. bulbosa and C. bulbosa var. lushii. Metabolomic analysis revealed spatial and differential accumulation of various metabolites. We chemically synthesized and characterized the cerpegin and its derivatives by liquid chromatography tandem-mass spectrometry (LC-MS/MS). Importantly, these comparisons suggested the presence of cerpegin and 5-allyl cerpegin in all C. bulbosa tissues. Further, de novo transcriptome analysis indicated the presence of significant transcripts for secondary metabolic pathways through the Kyoto encyclopedia of genes and genomes database. Tissue-specific profiling of transcripts and metabolites showed a significant correlation, suggesting the intricate mechanism of cerpegin biosynthesis. The expression of potential candidate genes from the proposed cerpegin biosynthetic pathway was further validated by qRT-PCR and NanoString nCounter. Overall, our findings propose a potential route of cerpegin biosynthesis. Identified transcripts and metabolites have built a foundation as new molecular resources that could facilitate future research on biosynthesis, regulation, and engineering of cerpegin or other important metabolites in such non-model plants.
Keywords: 5-Allyl cerpegin; Ceropegia; Cerpegin; LC-MS; metabolite; Transcriptome

Influence of domestication on specialized metabolic pathways in fruit crops - Dar, M. Saleem; Dholakia, Bhushan B.; Kulkarni, Abhijeet P.; Oak, Pranjali S.; Shanmugam, Dhanasekaran; Gupta, Vidya S.; Giri, Ashok P. (Planta, 2021)
Main conclusionDuring the process of plant domestication, the selection and traditional breeding for desired characters such as flavor, juiciness and nutritional value of fruits, probably have resulted in gain or loss of specialized metabolites contributing to these traits. Their appearance in fruits is likely due to the acquisition of novel and specialized metabolic pathways and their regulation, driven by systematic molecular evolutionary events facilitated by traditional breeding.AbstractPlants change their armory of specialized metabolism to adapt and survive in diverse ecosystems. This may occur through molecular evolutionary events, such as single nucleotide polymorphism, gene duplication and transposition, leading to convergent or divergent evolution of biosynthetic pathways producing such specialized metabolites. Breeding and selection for improved specific and desired traits (fruit size, color, taste, flavor, etc.) in fruit crops through conventional breeding approaches may further alter content and profile of specialized metabolites. Biosynthetic routes of these metabolites have been studied in various plants. Here, we explore the influence of plant domestication and breeding processes on the selection of biosynthetic pathways of favorable specialized metabolites in fruit crops. An orderly clustered arrangement of genes associated with their production is observed in many fruit crops. We further analyzed selection-based acquisition of specialized metabolic pathways comparing first the metabolic profiles and genes involved in their biosynthesis, followed by the genomic organization of such genes between wild and domesticated horticultural crops. Domestication of crop plants favored the acquisition and retention of metabolic pathways that enhanced the fruit value while eliminated those which produced toxic or unfavorable metabolites. Interestingly, unintentional reorganization of complex metabolic pathways by selection and traditional breeding processes has endowed us with flavorful, juicy and nutritionally rich fruits.
Keywords: Aroma; Domestication; Flavour; Fruit crops; Gene cluster; Specialized metabolites; Taste

Glance at the chemodiversity of Ocimum species: Trends, implications, and strategies for the quality and yield improvement of essential oil - Gurav, Tanuja P.; Dholakia, Bhushan B.; Giri, Ashok P. (Phytochemistry Reviews, 2022)
Ocimum species represent commercially important medicinal and aromatic plants. The essential oil biosynthesized by Ocimum species is enriched with specialized metabolites specifically, terpenoids and phenylpropanoids. Interestingly, various Ocimum species are known to exhibit diverse chemical profiles, and this chemical diversity has been at the center of many studies to identify commercially important chemotypes. Here, we present various chemotypes from the Ocimum species and emphasize trends, implications, and strategies for the quality and yield improvement of essential oil. Globally, many Ocimum species have been analyzed for their essential oil composition in over 50 countries. Asia represents the highest number of chemotypes, followed by Africa, South America, and Europe. Ocimum basilicum L. has been the most widespread and well-studied species, followed by O. gratissimum L., O. tenuiflorum L., O. canum Sims, O. americanum and O. kilimandscharicum Gurke. Moreover, various molecular reasons, benefits, adverse health effects and mechanisms behind this vast chemodiversity have been discussed. Different strategies of plant breeding, metabolic engineering, transgenic, and tissue-culture, along with anatomical modifications, are surveyed to enhance specific chemotypic profiles and essential oil yield in numerous Ocimum species. Consequently, chemical characterization of the essential oil obtained from Ocimum species has become indispensable for its proper utilization. The present chemodiversity knowledge from Ocimum species will help to exploit various applications in the industrial, agriculture, biopharmaceutical, and food sectors.
Keywords: Chemodiversity; Chemotype; Essential oil; Metabolic engineering; Ocimum; Specialized metabolites

Comprehensive tissue specific analysis of antioxidant potential and metabolite profiling of a vulnerable therapeutic herb Ceropegia sahyadrica - Pandey, Meena; Dholakia, Bhushan B.; Saraf, Purva S.; Punekar, Sachin A.; Giri, Ashok P. (3 Biotech, 2025)
This study investigated tissue-culture of an endangered medicinal herb, Ceropegia sahyadrica, along with tissue-specific variation in antioxidant activity and GC-MS based phytochemical profiling using wild and in vitro explants. In vitro leaf explants exhibited callus induction rate of 100% in Murashige and Skoog media containing 6-benzylaminopurine (4 mu M) and 2,4-dichlorophenoxyacetic acid (2 mu M) with 5% sucrose, whereas in vitro root explant achieved 66.7% with the combination of 2 mu M 6-benzylaminopurine and 1 mu M 2,4-dichlorophenoxyacetic acid in Murashige and Skoog medium. Microtuberization was most pronounced in in vitro root explants with a maximum response of 73.3% in 1 mu M indole-3-acetic acid, 2 mu M 6-benzylaminopurine and 5% sucrose. Scanning electron microscopy imaging revealed distinct cellular organization among tissues. Further, antioxidant potential assessed through 1,1-diphenyl-2-picrylhydrazyl radical scavenging assays and estimated total phenolic content showed metabolic variation and commonality between in vitro and wild tissues. Additionally, phytochemical profiling by gas chromatography-mass spectrometry identified 201 compounds, including alkaloids, fatty acid methyl esters, flavonoids, phytosterols and other bioactive molecules with alterations in metabolite profiles between in vitro and wild tissues. These findings demonstrated that explant origin and culture condition might significantly influence metabolic responses for conservation and ensures a reliable source of bioactive compound.
Keywords: Ceropegia- Conservation; Endemic medicinal herb; GC-MS; Metabolite profiling; Tuberization